Atypical Antiglomerular Basement Membrane Disease in a Pregnant Patient with Systemic Lupus Erythematosus - Areerat Ounhasuttiyanon; Ngoentra Tantranont; Thatsaphan Srithongkul (Case Reports in Nephrology)
Antiglomerular basement membrane disease (anti-GBM) is an unusual cause of glomerulonephritis. Patients usually present with rapidly progressive glomerulonephritis with or without pulmonary hemorrhage. The diagnosis is based on linear deposits of IgG along the GBM and the presence of anti-GBM antibodies. However, cases with atypical anti-GBM disease in which an anti-GBM antibody was not detected have been reported. We report a 29-year-old pregnant woman with underlying systemic lupus erythematosus (SLE) who presented with severe glomerulonephritis due to atypical antiglomerular basement membrane disease. She was initially diagnosed with active lupus nephritis and her renal function gradually worsened after steroid treatment, so the pregnancy was terminated due to the high maternal and fetal risks. A kidney biopsy showed linear capillary wall staining with fibrous crescents without endocapillary proliferation. The anti-GBM antibody showed negative results two times, so she was diagnosed with atypical anti-GBM disease. Treatment began with intravenous pulse methylprednisolone and continued with mycophenolate mofetil and prednisolone. Due to the intolerability of side effects, the treatment regimen was subsequently changed to intravenous cyclophosphamide. Although she had a significant improvement in clinical edema, serum albumin, and hematuria, her renal function gradually decreased during the 12 months of treatment. A review of the literature showed that the atypical anti-GBM is less aggressive than the typical anti-GBM disease. However, several patients had persistent renal dysfunction and 20–30% of patients had progression to ERSD. To the best of our knowledge, this is the first case of atypical anti-GBM disease in pregnant patients with suspected SLE reported in the literature.